2011
DOI: 10.1021/pr200621z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Protease Cleavage Sites Characterizes Prime and Non-prime Specificity of Cysteine Cathepsins B, L, and S

Abstract: Cysteine cathepsins mediate proteome homeostasis and have pivotal functions in diseases such as cancer. To better understand substrate recognition by cathepsins B, L, and S, we applied proteomic identification of protease cleavage sites (PICS) for simultaneous profiling of prime and non-prime specificity. PICS profiling of cathepsin B endopeptidase specificity highlights strong selectivity for glycine in P3' due to an occluding loop blocking access to the primed subsites. In P1', cathepsin B has a partial pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
157
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 109 publications
10
157
1
Order By: Relevance
“…The major difference in the structures of cathepsins L and B is that the latter contains a so-called occluding loop that covers part of the catalytic center, thereby limiting access of substrate proteins for endoproteolytic cleavage. Recently, the cleavage specificities of cathepsins B and L on naturally occurring peptides have been reassessed by the proteomic approach PICS (proteomic identification of protease cleavage sites [5,63]). Remarkably, the PICS cleavage site logo at pH 6 for cathepsin B contains 6 of the 8 amino acids present in the P4-P4= NiV F cleavage site.…”
Section: Discussionmentioning
confidence: 99%
“…The major difference in the structures of cathepsins L and B is that the latter contains a so-called occluding loop that covers part of the catalytic center, thereby limiting access of substrate proteins for endoproteolytic cleavage. Recently, the cleavage specificities of cathepsins B and L on naturally occurring peptides have been reassessed by the proteomic approach PICS (proteomic identification of protease cleavage sites [5,63]). Remarkably, the PICS cleavage site logo at pH 6 for cathepsin B contains 6 of the 8 amino acids present in the P4-P4= NiV F cleavage site.…”
Section: Discussionmentioning
confidence: 99%
“…We first determined whether Cat-S cleaved a decapeptide in which the P2, P1, and P1Ј positions were substituted: V 55 3 S, E 56 3 P, and T 57 3 K ( 52 GVTSPKVFSVD 62 ). As expected, Cat-S was unable to cleave this peptide at concentration up to 880 M (Fig.…”
Section: Cat-s Cleaves Par 2 Expressed In Hek Cells But Does Notmentioning
confidence: 99%
“…In experiments in HEK293 cells expressing PAR 2 with N-terminal Flag and C-terminal HA11 epitopes, we observed that Cat-S removed the extracellular Flag epitope, which indicates that Cat-S can cleave intact PAR 2 at the cell surface as well as receptor fragments. To ascertain the importance of cleavage at the E 56 2T 57 for Cat-S activation of PAR 2 , we studied the capacity of Cat-S to cleave and activate a mutant receptor in which the P2, P1 and P1Ј positions were replaced: V 55 Cat-S cleaves within the N terminus of PAR 2 is consistent with the known requirements for Cat-S substrate recognition (56,57). Aliphatic residues at the P2 position, including valine and leucine, direct Cat-S selectivity.…”
mentioning
confidence: 99%
“…They are potent ubiquitously expressed endopeptidases with broad substrate specificity that work best at acidic pH and reducing redox conditions 8,9 . Cathepsin L-deficient (Ctsl À / À ) mice reproduce normally, although pups showed a slightly increased mortality during the weaning period 10 .…”
mentioning
confidence: 99%